SOIL AMENDMENT BY HILUM ORIENTATION EFFECTS ON LEAF YIELD OF FLUTED PUMPKIN (Telfairia occidentalis Hook F.) - Mbah, E. U.; Ogidi, E. G. O.; Umesie, M. C. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
The effect of soil amendment by hilum orientation and their interactions on leafy yield of fluted pumpkin were investigated at the research farm, Michael Okpara University of Agriculture, Umudike, Nigeria. The experiment was laid out as 4 × 2 factorial arranged in a completely randomized design with eight treatment combinations. The experiment was replicated three times. The treatment factors comprised four types of soil amendment (200 kg ha-1 NPK fertilizer, 4 t ha-1poultry manure, 100 kg ha-1 NPK + 2 t ha-1 poultry manure and No fertilizer/Control) and two hilum orientations (hilum pointing up wards and hilum pointing down wards). The results from the analysis of variance on vine length, number of branches per plant, number of leaves per plant, length of internode and cumulative fresh leaf yield ha-1 indicated that the application of soil amendments and placement of fluted pumpkin hilum orientation techniques during planting significantly (P<0.05) impacted on the growth and yield parameters of the vegetable crop. The planting of fluted pumpkin with the hilum pointing downwards increased leafy yield relative to the hilum pointing up wards. The findings showed that soil amendment significantly increased leaf yield of fluted pumpkin in contrast to the hilum orientation main effect. The interaction treatment, 100 kg ha-1 NPK + 2 t ha-1 poultry manure × hilum pointing down wards produced (P<0.05) the highest cumulative fresh leaf yield, which was higher by 3.21 % relative to the application of 200 kg ha-1 NPK fertilizer × hilum pointing down wards treatment, which was the second highest cumulative leaf yield. There was a positive poly-linear relationship between vine length and leaf yield, number of branches per plant and leaf yield. The results indicated that this planting technique is encouraging, especially when the aim is to increase leaf yield in the production of fluted pumpkin. However, the findings from the study require further validation under field conditions.